2015
DOI: 10.1007/s10957-015-0711-2
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Inexact Proximal Algorithms: Routine’s Formation with Resistance to Change, Following Worthwhile Changes

Abstract: This paper shows how, in a quasi metric space, an inexact proximal algorithm with a generalized perturbation term appears to be a nice tool for Behavioral Sciences (Psychology, Economics, Management, Game theory,. . . ). More precisely, the new perturbation term represents an index of resistance to change, defined as a "curved enough" function of the quasi distance between two successive iterates.Using this behavioral point of view, the present paper shows how such a generalized inexact proximal algorithm can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…The question becomes: when a critical point is a variational trap. This point has been examined in Bento and Soubeyran [7]. In the case of weak resistance to change (the present paper) a striking result for applications in Behavioral Sciences has been to show how the strength of resistance to change can impact the speed of convergence of a habituation/routinization process; see [8].…”
Section: Resultsmentioning
confidence: 68%
See 3 more Smart Citations
“…The question becomes: when a critical point is a variational trap. This point has been examined in Bento and Soubeyran [7]. In the case of weak resistance to change (the present paper) a striking result for applications in Behavioral Sciences has been to show how the strength of resistance to change can impact the speed of convergence of a habituation/routinization process; see [8].…”
Section: Resultsmentioning
confidence: 68%
“…[7,8] have shown that generalized inexact proximal algorithms which use, at each period, a sufficient descent condition and a marginal stopping rule, represent a specific but leading prototype for the (VR) approach which allows to modelize, among many potential other applications, the formation and break of habits and routines. To save space, let us consider, in few terms, the example of hiring, firing and repeated employment routines, see [7], which represents a leading and concrete example in the vast literature on routine formation and break; see Feldman [16]. Consider an entrepreneur (leader) of an innovative firm who, at each period, can choose to hire and fire different kinds and numbers of skilled and specialized workers {1, 2, .…”
Section: Behavioral Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the general case C(x, y) = C(y, x), and C(x, x) 0 is possible. Hence, future research will examine the case where the Euclidean norm in (8) is replaced by a "like-distance" as done for instance in Bento and Soubeyran [3] and Moreno, Oliveira, and Soubeyran [43] for scalar-valued functions. This is better adapted to applications in behavioral sciences.…”
Section: Final Remarksmentioning
confidence: 99%